2011
DOI: 10.1128/mbio.00095-11
|View full text |Cite
|
Sign up to set email alerts
|

Diversion of the Immune Response to Neisseria gonorrhoeae from Th17 to Th1/Th2 by Treatment with Anti-Transforming Growth Factor β Antibody Generates Immunological Memory and Protective Immunity

Abstract: The immune response to Neisseria gonorrhoeae is poorly understood, but its extensive antigenic variability and resistance to complement are thought to allow it to evade destruction by the host’s immune defenses. We propose that N. gonorrhoeae also avoids inducing protective immune responses in the first place. We previously found that N. gonorrhoeae induces interleukin-17 (IL-17)-dependent innate responses in mice and suppresses Th1/Th2-dependent adaptive responses in murine cells in vitro through the inductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 31 publications
5
57
1
Order By: Relevance
“…Flow cytometric analysis demonstrated that inhibition of IL-10 and Tr1 cells resulted in enhanced Th1 and Th2 immune responses, indicated by significantly increased numbers of IFN-γ + /CD4 + ( p < 0.01) and IL-4 + /CD4 + T cells ( p < 0.05) in the ILN from treated mice in comparison to those from control mice (Figure 4e). In contrast to the effect of anti-TGF-β observed in our previous study, 14,15 anti-IL-10 did not hinder the Th17 response; instead it elevated the number of IL-17 + /CD4 + T cells ( p < 0.05) in ILN (Figure 4e). Similar results were observed in vaginas of the same mice.…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…Flow cytometric analysis demonstrated that inhibition of IL-10 and Tr1 cells resulted in enhanced Th1 and Th2 immune responses, indicated by significantly increased numbers of IFN-γ + /CD4 + ( p < 0.01) and IL-4 + /CD4 + T cells ( p < 0.05) in the ILN from treated mice in comparison to those from control mice (Figure 4e). In contrast to the effect of anti-TGF-β observed in our previous study, 14,15 anti-IL-10 did not hinder the Th17 response; instead it elevated the number of IL-17 + /CD4 + T cells ( p < 0.05) in ILN (Figure 4e). Similar results were observed in vaginas of the same mice.…”
Section: Resultscontrasting
confidence: 94%
“…13 In contrast, N. gonorrhoeae can selectively suppress Th1 and Th2 activity of mouse CD4 T cells, and induction of TGF-β plays a critical role in these differential effects. 14,15 Blockade of TGF-β diverts the pattern of host immune responses to N. gonorrhoeae and enhances specific protective immunity against the pathogen. However, we found that complete inhibition of TGF-β activity only partially reverses N. gonorrhoeae -mediated suppression of Th1 and Th2 cell proliferation and typical cytokine production.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that during experimental infection of the mouse, gonococcus induces an increase of regulatory T cells and infiltration of TGF- β 1 positive cells in the uterine stroma of infected animals [17], which may also be a mechanism of immune evasion as this type of T cells induces tolerance. Other, studies in a murine model demonstrated that N. gonorrhoeae enhances TGF- β 1 production and thereby promotes Th17-dependent response, with the consequent deployment of Th1/Th2 protective response [18]. Recent studies by Duncan and colleagues showed that N. gonorrhoeae suppresses the ability of dendritic cells (DC) to induce CD4+ T-cell proliferation and leads to upregulation of cell surface and secreted proteins with immunosuppressive properties [21].…”
Section: Discussionmentioning
confidence: 99%
“…This increase correlated with an augmenting of TGF- β 1-positive cells in the uterine stroma of infected animals [17]. Recent studies in the murine model of gonococcal genital tract infection showed that N. gonorrhoeae enhances TGF- β 1 production and thereby promotes Th17-dependent response with the consequent deployment of Th1/Th2 protective response [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Gene variants in this pathway could alter the immune response to N. gonorrhoeae as well as C. trachomatis . Mouse models have shown that N. gonorrhoeae induces TGF-β in order to suppress the host immune response and blockade of TGF-β improves host defense against this pathogen (25). Genes that regulate apoptosis can be manipulated by pathogens to increase the probability of replication and survival.…”
Section: Discussionmentioning
confidence: 99%